The coralline flora of a Miocene maerl : the Croatian "Litavac" - Basso, Daniela (Array, 2008)
Summary: The fossil coralline fl ora of the Badenian bioclastic limestone outcropping in Northern Croatia is known by the name “Litavac”, shortened from “Lithothamnium Limestone”. The name was given to indicate that unidentified coralline algae are the major component. In this first contribution to the knowledge of the coralline flora of the Litavac, Lithothamnion valens seems to be the most common species, with an unattached, branched growth-form. Small rhodoliths composed of Phymatolithon calcareum and Mesophyllum roveretoi also occur. The Badenian benthic association is dominated by melobesioid corallines, thus it can be compared with the modern maërl facies of the Atlantic Ocean and Mediterranean Sea. Since L. valens still survives in the present-day Mediterranean, an analogy between the Badenian Litavac and the living L. valens facies of the Mediterranean is suggested